The Wife of Bath’s Tales: Literary Characters as Social Persons in Historical Fiction - Hoggart, Carol Ann (Curtin University, 2019)
This thesis comprises an historical novel (The Jerusalem Tales) and an academic exegesis. The exegesis argues, as my creative practice demonstrates, that Elizabeth Fowler’s ‘social persons’ mode of analysis may facilitate the (re)creation of a complex literary character. The Wife of Bath from Chaucer’s Canterbury Tales is my case study. In the process of expanding Fowler’s theory to creative practice, the thesis offers a fresh interpretive approach to this much-analysed character from medieval literature.